2021
DOI: 10.1016/j.redox.2021.102108
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia induces endothelial dysfunction and accelerates atherosclerosis by disturbing the asymmetric dimethylarginine/dimethylarginine dimethylaminotransferase 2 pathway

Abstract: Hyperuricemia is closely associated with the mobility and mortality of patients with cardiovascular diseases. However, how hyperuricemia accelerates atherosclerosis progression is not well understood. The balance between asymmetric dimethylarginine (ADMA) and dimethylarginine dimethylaminotransferases (DDAHs) is crucial to regulate vascular homeostasis. Therefore, we investigated the role of the ADMA/DDAH pathway in hyperuricemia-induced endothelial dysfunction and atherosclerosis and the underlying molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“… 38–40 In this study, we focused on asymptomatic middle-aged and elderly participants because aging is considered as a chronic inflammatory state which plays a vital role in the pathogenesis and development of asymptomatic hyperuricemia and coronary calcification. 22 , 24 The results of our five-year follow-up and another observational study have shown that high serum uric acid levels are an independent risk factor for coronary calcification in asymptomatic middle-aged and elderly population. The relative mRNA expression levels in PBMCs of the four groups of patients (NC, HUA, CAC and HUA-CAC patients) were compared to verify the results of previous bioinformatics analysis on the common target genes of HUA and CAS.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“… 38–40 In this study, we focused on asymptomatic middle-aged and elderly participants because aging is considered as a chronic inflammatory state which plays a vital role in the pathogenesis and development of asymptomatic hyperuricemia and coronary calcification. 22 , 24 The results of our five-year follow-up and another observational study have shown that high serum uric acid levels are an independent risk factor for coronary calcification in asymptomatic middle-aged and elderly population. The relative mRNA expression levels in PBMCs of the four groups of patients (NC, HUA, CAC and HUA-CAC patients) were compared to verify the results of previous bioinformatics analysis on the common target genes of HUA and CAS.…”
Section: Discussionmentioning
confidence: 74%
“… 22 , 23 Meanwhile, many studies have shown that the pathogenesis of HUA is related to inflammation, oxidative stress, insulin resistance and so on. 8 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice and research, HUA is generally reported when the serum urate is above 0.42 mmol/L (7 mg/dl) for men or 0.36 mmol/L (6 mg/dl) for women ( 4 ). It may result in the deposition of UA crystals, which promotes high comorbidity burden and finally leads to tissue damage such as gout ( 5 ), atherosclerosis ( 6 ), type 2 diabetes mellitus ( 7 ), vascular damage ( 8 ), and chronic kidney disease ( 9 ). The incidence of HUA has been remarkably increased by about 20% worldwide ( 10 ), and the patients have become younger, which is of concern ( 11 , 12 ), so HUA has emerged as a public health challenge.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study in patients with unilateral small kidney or renal agenesis conducted by Yazici et al demonstrated that the SUA level was positively correlated with arterial stiffness ( Yazici et al, 19932017 ). Mechanistic studies have shown that uric acid causes endothelial dysfunction, resulting in cardiovascular events ( Khosla et al, 2005 ; Liang et al, 2015 ; Lee et al, 2021 ; Singh et al, 2021 ). In our meta-analysis, we found that allopurinol might slightly reduce the risk of cardiovascular complications in only three RCTs.…”
Section: Discussionmentioning
confidence: 99%